El control judicial en el orden federal argentino, luego de la reforma de Ley Bases 27.742 - Rey Vázquez, Luis Eduardo (2025)
The main reforms carried out at the national level in the Argentine Republic to the regime of exhaustion of the administrative route, aimed at accessing the judicial instance, through the so-called Basic Law, are presented, making a recount of the reappearance of some previously existing institutes that were repealed during the more than 50 years of validity of the National Law of Administrative Procedures, concluding with an expansion of the legal sphere of protection of the individual against state action.